Design of Picohydro Power Plant for Application of River-based Garbage Lifting Tool IoT - Dudiawan, Dudiawan; machdi, agustini rodiah; notosudjono, didik (Teknik Elektro Universitas Siliwangi, 2025)
Utilizing water energy can be implemented on small scale, such as with a (PLTPH), which is a small-scale power plant using water as its driving force through a penstock to move a turbine. By applying a river trash lifter based on IoT, the cleanliness of the river environment can be managed. the power source comes from a generator coupled to a Pelton turbine type, which will rotate the generator to produce VAC electricity that will first be converted to VDC voltage so that the voltage is more stable and then converted back to 220 VAC voltage by an inverter. This will become the main energy source for the IoT-based river trash lifter using the Wemos D1 R1 microcontroller as the system's brain to control and collect data from two HC-SR04 ultrasonic sensors, which will be monitored on an LCD display and Telegram notifications. Test results show that water pressure greatly affects the performance of the PLTMH prototype design, with a minimum water pressure required for the PLTMH to work being 18 psi. The generator can produce 60 VAC voltage with an average voltage of 50.05 VAC and an average generator current of 0.046 amps. The power on the generator depends on the voltage and current produced. The load on the generator after being converted to DC current is 9 watts. The duration of the conveyor operation to lift trash from the river to the collection bin depends on the HC-SR04 ultrasonic sensor placed in the river when it detects trash, which will be displayed on the LCD. When the collection bin is full, the HC-SR04 ultrasonic sensor in the collection bin will activate a buzzer, which will be displayed on the LCD and the ThingSpeak.